Hydrogen sulfide (H2S) conversion to hydrogen (H2) and value-added chemicals : Progress, challenges and outlook - Chan, Yi Herng; Adrian Chun Minh, Loy; Cheah, Kin Wai; Slyvester Yew Wang, Chai; Ngu, Lock Hei; How, Bing Shen; Claudia, Li; Serene Sow Mun, Lock; Wong, Mee Kee; Yiin, Chung Loong; Bridgid Lai Fui, Chin; Chan, Zhe Phak; et al. (Elsevier, 2023)
Hydrogen sulfide (H2S) is a toxic gas released from natural occurrences (such as volcanoes, hot springs, municipal waste decomposition) and human economic activities (such as natural gas treatment and biogas production). Even at very low concentrations, H2S can cause adverse health impacts and fatality. As such, the containment and proper management of H2S is of paramount importance. The recovered H2S can then be transformed into hydrogen (H2) and various value-added products as a major step towards sustainability and circular economy. In this review, the state-of-the-art technologies for H2S conversion and utilization are reviewed and discussed. Claus process is an industrially established and matured technology used in converting H2S to sulfur and sulfuric acid. However, the process is energy intensive and emits CO2 and SO2. This calls for more sustainable and energy-efficient H2S conversion technologies. In particular, recent technologies for H2S conversion via thermal, biological, plasma (thermal and non-thermal), electrochemical and photocatalytic routes, are critically reviewed with respect to their strengths and limitations. Besides, the potential of diversified value-added products derived from H2S, such as H2, syngas, carbon disulfide (CS2), ammonium sulphate ((NH4)2SO4), ammonium thiosulfate ((NH4)2S2O3), methyl mercaptan (CH3SH) and ethylene (C2H4) are elucidated in detail with respect to the technology readiness level, market demand of products, technical requirements and environmental impacts. Lastly, the technological gaps and way forward for each technology are also outlined.